A Critical Review on Synthesis of Aluminum Metallic Composites through Stir Casting: Challenges and Opportunities. Issue 10 (26th July 2020) - Singh, Ashish Kumar; Soni, Sanjay; Rana, Ravindra Singh
Abstract : Aluminum metallic composites (AMCs) have been recognized as promising material exhibiting excellent functional and structural properties that can be significantly tailored to meet the industrial demands as well as to meet the design criteria for many applications such as aerospace, automobiles, marine, defense, and so on. Herein, an effort is made to provide an extensive overview of the various processing techniques adopted for the development of AMCs. Various processing kinetics of stir casting technique are elaborated comprehensively in terms of existing challenges, conceivable modifications incorporated in it. Considering the critical assessment on mechanical properties made through various kinds of literature, an electromagnetic stir‐squeeze casting synergically equipped with ultrasonic transducing probe and bottom pouring attachments is recommended as the most appropriate processing technique for the development of AMCs. Moreover, appropriate recommendations regarding process variables and additives/modifiers, and potential future research opportunities are also addressed significantly to encourage the ongoing and upcoming researchers, which lead this critical Review toward novelty and uniqueness. Abstract : Herein, aluminum metallic composites (AMCs) with their constituents are introduced. It schematically describes various processing techniques of AMCs. It critically assesses and emphasizes stir casting explicitly enlightening challenges and conceivable modifications. It recommends various process variables and additives. It highlights the various attributes of stir casting through an Ishikawa diagram and proposes concluding remarks with future research opportunities.